The Effect of Labor Unions on CEO Compensation - Huang, Qianqian; Jiang, Feng; Lie, Erik; Que, Tingting (Journal of Financial and Quantitative Analysis, 2017)
We find evidence that labor unions affect chief executive officer (CEO) compensation. First, we find that firms with strong unions pay their CEOs less. The negative effect is robust to various tests for endogeneity, including cross-sectional variations and a regression discontinuity design. Second, we find that CEO compensation is curbed before union contract negotiations, especially when the compensation is discretionary and the unions have a strong bargaining position. Third, we report that curbing CEO compensation mitigates the chance of a labor strike, thus providing a rationale for firms to pay CEOs less when facing strong unions.